Echoes of Soviet urbanism exploring modernist housing narratives : perspectives on heritage, transformation, and community : dynamics in East European and Eurasian Microrayons - Engel, Barbara 1969- (DOM publishers, 2024)
"The book ... presents thirteen ‘district stories’ from seven post-Soviet countries, written by experts from a variety of disciplines, including architecture, urban and regional planning, public policy and social sciences, and human geography. The authors present observations of spatial, social, and functional transformations as well as of the formal and informal frameworks, planning strategies, and concepts that lay behind the physical development. They discuss spatial patterns and their modifications with a view to future heritage-sensitive development of the neighbourhoods. They point out unique details and the fact that genius loci makes a difference. The contributions formulate new narratives for large housing estates from the 1960s and identify the potential challenges in responsible planning and the need for action." (Klappentext)
Keywords: Geschichte 1960-2020; Großtafelbau; Geschossbau; Städtebau; Wohnungsbau; Architektur; Osteuropa; Sowjetunion; Aufsatzsammlung